Global upper ocean dissolved oxygen budget for constraining the biological carbon pump - Ryohei Yamaguchi; Shinya Kouketsu; Naohiro Kosugi; Masao Ishii (Communications Earth & Environment)
Abstract One mechanism by which the ocean uptakes carbon dioxide is through the biological carbon fixation and its subsequent transport to the deep ocean, a process known as the biological carbon pump. Although the importance of the biological pump in the global carbon cycle has long been recognized, its actual contribution remains uncertain. Here, we quantify the carbon export from the upper ocean via the biological carbon pump by revealing the upper ocean dissolved oxygen balance. Calculations of dissolved oxygen budget quantified net oxygen removals from the upper ocean by physical processes (air–sea exchange, advection, and diffusion) and indicated net biological oxygen production that compensated for those removals. The derived oxygen production is converted to carbon units using the photosynthetic ratio, and inferred an estimated global annual carbon export through the biological pump of 7.36 ± 2.12 Pg C year−1 with providing insights into the overall ocean carbon cycle.